The Correlation Between Podcast Media and Listening Achievement in Grade IX Students at SMPI Al Mukhlisin Pakong Pamekasan - Bela Millatin Nadzifah; Arisandi Setiyawan; Fitrah Yuliawati (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study examines the relationship between the use of podcast media and the listening achievement of grade IX students at SMPI Al Mukhlisin Pakong Pamekasan. Many students struggle to comprehend spoken English, especially when listening to native speakers. To address this issue, a correlational quantitative research method was employed, utilizing observation, interviews, questionnaires, tests, and documentation as research instruments. The collected data from questionnaires and tests were analyzed using the Pearson Product Moment correlation test with SPSS 17. The results indicate a positive and significant correlation between podcast use and students' listening achievement, with an r-value of 0.413 and a significance value of 0.023 (p < 0.05). Although the correlation falls into the moderate category, these findings suggest that podcasts can serve as an effective learning tool for enhancing students’ listening skills. Therefore, integrating podcasts with other instructional methods is recommended for more optimal learning outcomes. This study contributes to the development of technology-based learning strategies that align with students' needs in the digital era